Analysis of Cultural Literacy Skills of PGSD Students in Ethnoscience Learning Courses - Ardianti*, Sekar Dwi; Fardani, Much Arsyad; Kironoratri, Lintang; Tanghal, Analiza B (Jurnal IPA & Pembelajaran IPA, 2025)
Cultural literacy is an important skill that involves understanding the cultural values, norms, and traditions that exist in society. Ethnoscience learning, which combines scientific knowledge with local wisdom, is expected to be one of the means to improve the cultural literacy of PGSD students. This study aims to analyze the cultural literacy skills of PGSD students in ethnoscience courses and provide references for the development of learning activities in the future. The method used is quantitative research with a survey approach with a sample of 60 seventh semester students who have taken ethnoscience courses. Data collection techniques are interviews, observations, tests in the form of questionnaires, and documentation. The results obtained showed that the ability of cultural literacy in ethnoscience courses applied to PGSD UMK students was the highest percentage with good assessment criteria obtained by 39 students out of a total of 60 students with a percentage of 65%. The conclusion of this study is that the cultural literacy skills of PGSD students in ethnoscience learning courses can be categorized as good